APPLICATION OF ARTIFICIAL INTELLIGENCE IN ADOLESCENT MENTAL HEALTH SUPPORT: A QUALITATIVE STUDY IN CHINESE MIDDLE SCHOOLS - Liu , Xingchen; Lee , Keok Cheong (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2025)
This study explores the anticipated role of Artificial Intelligence (AI) in supporting adolescent mental health in Chinese secondary schools. Traditional school-based counseling is often hindered by limited resources and stigma. AI tools, including chatbots, emotion recognition, and virtual counseling platforms, may offer scalable alternatives. This study will use a qualitative design, this research plan to collect data from students, teachers, and parents across three provinces through interviews, questionnaires, and observations. It is anticipated that AI tools will enhance early risk detection, emotional expression, and accessibility to psychological support. It is expected that students will value the privacy of chatbots, while teachers and parents may recognize AI’s potential in behavioral monitoring and guidance. However, possible concerns around ethics, trust, and cultural acceptance are also predicted. The study aims to explore whether emotional AI will be particularly effective in contexts where human counseling is limited. Recommendations are expected to include strategies for integrating AI into school systems with ethical safeguards and local adaptability.